Strategi Kepemimpinan dalam Menghadapi Pandemi Covid-19 pada Kasus Coffee Shop Contou - Nurjihan Dwi T, Anindita; Hermanto, Bambang; Wulan Tresna, Pratami (Program Studi Manajemen FEBM UMRAH, 2022)
On March 10, 2020, the start of the Covid-19 pandemic caused an impact that was felt by several countries, even the government and society. One of the impacts felt was not only a health problem but also attacking the country's economy, for example MSMEs as the Micro, Small and Medium Enterprises sector experienced a severe impact due to the Covid-19 pandemic. Based on information processed by LIPI's P2E, the impact of tourism shrinkage on MSMEs engaged in the micro food and beverage business reached 27%. While the impact on small food and beverage businesses is 1.77% and medium enterprises is 0.07%. Contou is one of the coffee shops that has been affected by the Covid-19 pandemic, but it's great that they were able to fight this crisis so that in 2021 Contou will still continue to operate with the strategies they created to survive. After understanding the five theories above, the owner of Contou coffee can be categorized as a leader who adheres to an adaptive leadership strategy. Where, covid-19 is an unexpected event that is not predicted in advance and affects activities at Contou coffee which are based on various health policies to deal with covid-19.